KNOWLEDGE AT THE HIGHER EDUCATION INSTITUTION - CICHON, Seweryn (Trends in education, 2013)
The knowledge created within the higher education institution becomes the primary source of its economic value, and built its competitive advantage by continuously changing environment. The knowledge of the higher education institution is supposed to be created, acquired, handed over and use defectively promoting faster economic and social development. And so surrounding expects the today's higher education institution of creating the modern knowledge. Knowledge is valuable when it is delivered in the right way, to the right people at the right time.
Keywords: knowledge; higher education institution; community